Comparison of the Anticoagulant and Antithrombotic Effects of Synthetic Thrombin and Factor Xa Inhibitors - Hauptmann, J; Kaiser, B; Nowak, G; Stürzebecher, J; Markwardt, F (Thrombosis and Haemostasis, 1990)
The anticoagulant effect of selected synthetic inhibitors of thrombin and factor Xa was studied in vitro in commonly used clotting assays. The concentrations of the compounds doubling the clotting time in the various assays were mainly dependent on their thrombin inhibitory activity. Factor Xa inhibitors were somewhat more effective in prolonging the prothrombin time compared to the activated partial thromboplastin time, whereas the opposite was true of thrombin inhibitors.In vivo, in a venous stasis thrombosis model and a thromboplastin-induced microthrombosis model in rats the thrombin inhibitors were effective antithrombotically whereas factor Xa inhibitors of numerically similar IQ value for the respective enzyme were not effective at equimolar dosageThe results are discussed in the light of the different prelequisiles and conditions for inhibition of thrombin and factor Xa in the course of blood clotting.